Tożsamość i wolność w perspektywie postkolonializmu w Mimesis Pawła Huellego - Palian-Kobiela, Ewelina (Postscriptum Polonistyczne, 2020)
The aim of this work is to interpret – by means of the postcolonial strategy of reading – a short story titled Mimesis, published in Paweł Huelle’s collection: Opowieści chłodnego morza. This kind of interpretation reveals a choice of new perspectives, aiming at the healing of trauma by explaining the symptoms and revealing hidden facts. In Mimesis by Huelle, this happens due to the character’s narration. The author of the article presents a process of the characters identity creation during their encounters with different cultures (Huelle exemplifies a multicultural mosaic in his short story). All the way through the imagery of the characters, the author of the article enhances the main axiological features and describes the process of identity creation, thus an act of liberating oneself from restrictions of one’s own culture.